INFLUENCE OF WORK CULTURE, WORK DISCIPLINE, AND IMPLEMENTATION OF STANDARD OPERATING PROCEDURE (SOP) ON ASN PERFORMANCE AT THE REGIONAL SECRETARIAT OF WEST SUMATRA PROVINCE - Frinaldi, Aldri; Putra, Nanda (CosmoGov: Jurnal Ilmu Pemerintahan, 2025)
The aim is to analyze the effect of work culture and discipline on the implementation of SOP, the influence of work culture, discipline, and the application of SOP on ASN performance, the influence of work culture on performance through the application of SOP, and the influence of work discipline on ASN performance through the application of SOP as an intervening variable. The method used is an associative quantitative method. The ASN population at the Regional Secretariat of the Province of West Sumatra, comprising 188 people, was sampled using a probability random sampling technique. The path analysis test was conducted using a closed-ended questionnaire instrument, which was analyzed using SPSS 24.0 software. The results of the data analysis show that work culture and discipline have a significant effect on the implementation of SOP. There is a substantial influence of work culture, discipline, and the application of SOPs on ASN performance. Then, the work culture indirectly, through the implementation of SOPs, doesn’t have a significant effect on ASN performance, and the influence of work culture on performance through the implementation of SOPs. The implementation of SOP has no considerable impact on ASN performance at the Regional Secretariat of West Sumatra Province.gb777